Possible northern persistence of Siebold’s beech, Fagus crenata, at its northernmost distribution limit on an island in Japan Sea: Okushiri Island, Hokkaido - Kitamura, Keiko; Namikawa, Kanji; Tsuda, Yoshiaki; Kobayashi, Makoto; Matsui, Tetsuya (Frontiers in Plant Science, 2022)
Siebold’s beech, Fagus crenata, is widely distributed across the Japanese Archipelago and islands in the Sea of Japan. Similar to the northern limit of the geographical distribution of F. crenata on the mainland of Hokkaido, the northern limit of the distribution of F. crenata on islands in the Japan Sea is observed on Okushiri Island (ca 42°N). To understand the genetic relationships of F. crenata on Okushiri Island, we examined chloroplast (cp) DNA haplotypes and 11 nuclear microsatellite (SSR) loci among 1,838 individuals from 44 populations from Okushiri Island, mainland Hokkaido, and the northern part of the Tohoku region on Honshu Island. We identified 2 cpDNA haplotypes, which represent not only populations on the Japan Sea coast but also those on the Pacific coast and this suggested the Okushiri Island populations might not be formed by single colonization. Genetic diversity of the Okushiri populations of nuclear SSR was not lower than the mainland and the STRUCTURE analysis revealed the Okushiri Island individuals were admixed between Hokkaido and Tohoku clusters. Approximate Bayesian computation inferred that divergence between Tohoku and Hokkaido, and admixture which generated Okushiri populations occurred 7,890 (95% hyper probability density (HPD): 3,420 – 9910) and 3870 (95% HPD: 431– 8,540) generations ago, respectively, predating to the last glacial maximum (LGM). These inferences were well supported by a geological history which suggested an isolation of Okushiri Island from Hokkaido started prior to the Middle Pleistocene. We discuss the possible persistence of F. crenata during the last glacial maximum on northern islands in the Japan Sea such as Okushiri Island.